Strategy for Increasing the Absorption of Revenue Sharing Fund of Reforestation Fund in East Kalimantan Province Government - Nugraha, Ramlan -; Hakim, Dedi Budiman; Falatehan, A. Faroby (JURNAL MANAJEMEN AGRIBISNIS; Vol 12 No 1 (2024): Jurnal Manajemen Agribisnis, 2024)
Revenue sharing fund of reforestation fund (DBH DR) is one source of regional revenue from natural resources. However, since distributed to provinces in 2017, they have problems every years in absorbing this funds. In 2017-2019, there is still remaining funds of 1.4 trillion from the 2.47 trillion has distributed to the provinces. This study aims to analyze the policies and implementation of DBH DR, as well as identify the factors that influence the absorption of the budget based on stakeholder perceptions. The survey was conducted with key stakeholders in East Kalimantan Province, Ministries and the community to find out their perceptions of program implementation and was analyzed using the NVivo 12 application. Based on research, technical regulations issued by the central government have not accommodated regional needs. The planning time for DBH DR is not in accordance with the regional planning and budgeting cycle, resulting in adjustments and delays in the activities implementation. The strategy is synchronization of DBH DR policies or regulations with regional planning and budgeting cycles, expanding the use of DBH DR according to regional needs, and capacity building for local government officials on technical regulations.